2010
DOI: 10.1016/j.cellimm.2010.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and functional activity of Th17, Tc17 and other T-cell subsets in Systemic Lupus Erythematosus

Abstract: a b s t r a c tTo compare frequency and functional activity of peripheral blood (PB) Th(c)17, Th(c)1 and Treg cells and the amount of type 2 cytokines mRNA we recruited SLE patients in active (n = 15) and inactive disease (n = 19) and healthy age-and gender-matched controls (n = 15). The study of Th(c)17, Th(c)1 and Treg cells was done by flow cytometry and cytokine mRNA by real-time PCR. Compared to NC, SLE patients present an increased proportion of Th(c)17 cells, but with lower amounts of IL-17 per cell and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
68
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 49 publications
(60 reference statements)
10
68
2
Order By: Relevance
“…3). Actually, in line with the notable cytokine profile plasticity presented by normal peripheral Th17 cells and taking into account the enhancement of Th2 cell function found previously by us in active SLE patients, [28] along with the miscellaneous immunosuppressive drugs received by those patients [29,30], a suppressive effect may be exerted on Th17 polyfunctional effector phenotype, resulting in a decrease proportion of those subpopulations expressing TNF-α/IL-2 and TNF-α. Especially, those findings may point to the strong fidelity lineage of Th17 in active disease SLE or even a terminal differentiation stage related with a repeated antigen challenge as compared to inactive SLE or normal control groups.…”
Section: Discussionsupporting
confidence: 67%
“…3). Actually, in line with the notable cytokine profile plasticity presented by normal peripheral Th17 cells and taking into account the enhancement of Th2 cell function found previously by us in active SLE patients, [28] along with the miscellaneous immunosuppressive drugs received by those patients [29,30], a suppressive effect may be exerted on Th17 polyfunctional effector phenotype, resulting in a decrease proportion of those subpopulations expressing TNF-α/IL-2 and TNF-α. Especially, those findings may point to the strong fidelity lineage of Th17 in active disease SLE or even a terminal differentiation stage related with a repeated antigen challenge as compared to inactive SLE or normal control groups.…”
Section: Discussionsupporting
confidence: 67%
“…Recently, a subpopulation of CD8 + T cells, a cell subset producing IL-17 (Tc17), was also discovered. [5][6][7] In addition, Henriques et al [8] reported that a trend for increased proportion in Tc17 cells was found in systemic lupus erythematosus (SLE) patients when they were compared with healthy controls. Furthermore, Ortega et al [9] showed that IL-17-producing CD8 + T lymphocytes from psoriasis skin plaques are cytotoxic effector cells that secrete Th17-related cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Th17 cells have been implicated in the pathogenesis of several human autoimmune diseases and inflammatory disease models via proinflammatory cytokines production [20][21][22][23]. On the other hand, Th17 cells play an important role in host defense against extracellular bacteria and parasites [24].…”
Section: Gut Microbiota and Th17mentioning
confidence: 99%